1
$\begingroup$

In the Laplace domain, we have this: $$X_1(s) = \frac{1}{s+4}(U(s)-X_2(s))$$ I want to get this by: $$\dot x_1(t) = -4x_1(t) + u(t)-x_2(t)$$ This is done by rearranging the first equation into: $$(s+4)X_1(s) = U(s)-X_2(s)$$ Then take the Inverse Laplace Transform on both sides. However, I would like know if I could achieve the same thing without rearranging the equation 1 first. Taking the Inverse Laplace Transform directly on both sides of the first equation resulting: $$x_1(t) = e^{-4t}(u(t)-x_2(t))$$ Then take derivative with respect to $t$ on both sides: $$\dot x_1(t) = -4e^{-4t}(u(t)-x_2(t)) + e^{-4t}(\dot u(t)-\dot x_2(t))$$ $$\dot x_1(t) = -4x_1 + e^{-4t}(\dot u(t)-\dot x_2(t))$$

I got stuck here. If this cannot be converted to the desired form, what is the reason for this?

$\endgroup$

1 Answer 1

1
$\begingroup$

The Mistake

Your mistake is here:

$$ X_1(s) = \frac{1}{s+4} \cdot(U(s)-X_2(s)) \xrightarrow{\mathscr{L}^{\,-1}} x_1(t) = e^{-4t}\cdot(u(t)-x_2(t)) $$

In doing so, you have implicitly assumed the following equality as true:

$$ \color{red}{ \mathscr{L}^{-1} \left[ F(s) \cdot G(s) \right] = f(t) \cdot g(t)} \qquad \text{(Wrong!)} $$


The Right Way

The correct version involves the convolution integral:

$$ \bbox[5px,border:1.1px solid black] { \mathscr{L}^{-1} \left[ F(s) \cdot G(s) \right] = \left( {f * g} \right)\left( t \right) = \int_{{0}}^{{t}}{{f( {t - \tau } )g\left( \tau \right)\,d\tau }} } $$ (Note that a convolution operation in time domain corresponds to a multiplication operation in Laplace complex frequency domain)

So, for your example:

$$ \begin{alignat}{1} \mathscr{L}^{-1}[X_1(s)] = \mathscr{L}^{-1}\left[ \frac{1}{s+4} \cdot (U(s)-X_2(s)) \right] \end{alignat} $$

Then:

$$ \begin{alignat}{1} x_1(t) = \int_{{0}}^{{t}}{{e^{-4(t - \tau)} \cdot \left( u(\tau) - x_2(\tau) \right)\,d\tau }} \implies \dot{x}_1(t) &= \dfrac{d}{dt} \int_{{0}}^{{t}}{{e^{-4(t - \tau)} \cdot \left( u(\tau) - x_2(\tau) \right)\,d\tau }} \end{alignat} $$

I don't think there is a way to get to the original differential equation from here without knowing nothing about $u(t)$ and $x_2(t)$. But if you choose two functions and solve this integral, it will lead to the same result given by the Inverse Laplace Transform operation without convolution.


An Example

Let's pick $u(t) = cos(t)$ and $x_2(t) = e^{-t}$. Then, we have $\mathscr{L} \left[u(t)-x_2(t) \right] = \dfrac{s-1}{s^3+s^2+s+1}$

  • Anti-transforming without using convolution:

$$ X_1(s) = \dfrac{s-1}{(s+4)\cdot(s^3+s^2+s+1)} = \frac{-1/3\,}{s+1} + \frac{5/51}{s+4} + \frac{(4s+1)/17}{s^2+2} \\[30px] \begin{alignat}{1} x_1(t) &= -\frac{1}{3}e^{-t} + \frac{5}{51}e^{-4t}+\frac{1}{17}\left(4\cos(t) + \sin(t) \right) \\[5px] \dot{x}_1(t) &= +\frac{1}{3}e^{-t} + \frac{20}{51}e^{-4t}+\frac{1}{17}\left(\cos(t) -4\sin(t) \right) \end{alignat} $$

  • Anti-transforming using convolution:

$$ X_1(s) = \bigg(\frac{1}{s+4}\bigg) \cdot \bigg(\frac{s-1}{s^3+s^2+s+1}\bigg) \\[30px] \begin{alignat}{1} \dot{x}_1(t) = \dfrac{d}{dt} \int_{{0}}^{{t}}{{e^{-4(t - \tau)} \cdot \left( \cos(\tau) - e^{-\tau} \right)\,d\tau }} \,=\, \frac{1}{3}e^{-t} + \frac{20}{51}e^{-4t}+\frac{1}{17}\left(\cos(t) -4\sin(t) \right) \end{alignat} $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.